Association between diastolic cardiac dysfunction and nonalcoholic fatty liver disease: A systematic review and meta-analysis - Karn Wijarnpreecha (2018)
© 2018 Editrice Gastroenterologica Italiana S.r.l. Background/objectives: Recent studies have suggested an association between nonalcoholic fatty liver disease (NAFLD) and diastolic cardiac dysfunction, although the results were inconsistent. This study was conducted to investigate this possible association. Methods: A comprehensive literature review was conducted utilizing the MEDLINE and Embase databases from inception through May 2018 to identify all cross-sectional studies that compared the prevalence of diastolic cardiac dysfunction among patients with NAFLD to individuals without NAFLD. Effect estimates from each study were extracted and combined using the random-effect, generic inverse variance method of DerSimonian and Laird. Results: A total of 12 studies with 280,645 participants fulfilled the eligibility criteria and were included in the meta-analysis. There was a significant association between NAFLD and diastolic cardiac dysfunction with a pooled odds ratio (OR) of 2.02 (95% confidence interval (CI), 1.47–2.79; I2 89%). Subgroup analysis based on the country of origin continued to demonstrate a significant association in subgroups of both Western and Eastern countries with pooled ORs of 1.76 (95% CI, 1.14–2.72; I2 85%) and 2.59 (95% CI, 1.42–4.69; I2 87%), respectively. Limitations included high between-study heterogeneity, lack of unified definition of diastolic dysfunction and presence of publication bias. Conclusions: A significant association between diastolic cardiac dysfunction and NAFLD was observed in this meta-analysis. This observation could suggest the need for careful cardiovascular surveillance among patients with NAFLD.